Indonesian generative chatbot model for student services using GPT - Priccilia, Shania; Girsang, Abba Suganda (International Journal of Informatics and Communication Technology (IJ-ICT), 2024)
The accessibility of academic information greatly impacts the satisfaction and loyalty of university students. However, limited university resources often hinder students from conveniently accessing information services. To address this challenge, this research proposes the digitization of the question-answering process between students and student service staff through the implementation of generative chatbot. A generative chatbot can provide students with human-like responses to academic inquiries at their convenience. This research developed generative chatbot using pre-trained GPT-2 architecture in three different sizes, specifically designed for addressing practicum-related questions in a private university in Indonesia. The experiment utilized 1288 question-answer pairs in Indonesian and demonstrated the best performance with a BLEU score of 0.753, signifying good performance accuracy in generating text despite dataset limitations.